Importance Of Dooshivisha In Current Era W.S.R. To Chemical Toxicity Of Food. - Godara, Sunita; Upadhyay, Parmanand; Sharma, Anita (International Research Journal of Ayurveda & Yoga, 2020)
Food is fundamental importance to life. Chemicals are used in every step of the process that puts food on our table: production, harvesting, processing, packing, transport, marketing and consumption and can be dangerous to our health. These chemicals like pesticides, fertilizers, food preservatives and adulterants, artificial sweeteners, emulsifiers, flavours and artificial fruit ripening chemicals remain in our food and many persist in the environment and our bodies for decades to come. We cannot avoid toxicants in our food completely, but we can do many things to reduce their exposure. This concept is explained in Ayurveda in Dooshivisha prakrana. By using this concept, we can properly understand different type of food toxicities due to various chemicals present in our food and treat them by using the principles of Ayurveda.